Insights on Public Health Professionals Non-technical Skills in an Emergency Response (Multi-Team System) Environment - Black, Andrew; Brown, Olivia; Utunen, Heini; Gamhewage, Gaya; Gore, Julie (Frontiers in Psychology, 2022)
This perspectives paper provides practitioner and academic insights into the importance of examining non technical skills (NTS) in emergency response environments, which we suggest are viewed as multiteam systems for improved response. The case of public health professionals are highlighted, illustrated with unique qualitative field data which focused upon the use of non-technical skills at a meso level of analysis. Results reflect upon the importance of understanding public health professionals as acting within a multi-team environment, and focus upon NTS including, communication, decision making, leadership, resilience, network relationship building, and sensemaking. Recommendations for future research with this hard to access professional group are located within emerging advances in the scientific inquiry of complex and increasingly evident, multi-team systems.